Representation of Unrequited Love: Barthes' Semiotics Study in the Selected Songs of The Secret of Us Album by Gracie Abrams - Agustin, Faira Tri; Hkikmat, Mahi M.; Nur Sakinah, R Myrna (Universitas Muhammadiyah Mataram, 2025)
This research is important because it examines how unrequited love, a common emotional phenomenon experienced by many people, is represented in the lyrics of popular songs and can affect the emotional understanding of listeners. The purpose of this study is to analyze the representation of unrequited love in three selected songs from Gracie Abrams' The Secret of Us album using Roland Barthes' semiotic approach. The research method used is descriptive qualitative. Data were collected through documentation of song lyrics and analyzed using Barthes' semiotic approach, which are denotation, connotation and myth. The results are based on Bringle's theory that Close to You and Felt Good About You belong to the category of unequal love, while Let It Happen belongs to the category of pursuing the love object.